Ionic electroactive hybrid transducers - Akle, Barbar J. (2017)
Ionic electroactive actuators have received considerable attention in the past ten years. Ionic electroactive polymers, sometimes referred to as artificial muscles, have the ability to generate large bending strain and moderate stress at low applied voltages. Typical types of ionic electroactive polymer transducers include ionic polymers, conducting polymers, and carbon nanotubes. Preliminary research combining multiple types of materials proved to enhance certain transduction properties such as speed of response, maximum strain, or quasi-static actuation. Recently it was demonstrated that ionomer-ionic liquid transducers can operate in air for long periods of time (>250,000 cycles) and showed potential to reduce or eliminate the back-relaxation issue associated with ionomeric polymers. In addition, ionic liquids have higher electrical stability window than those operated with water as the solvent thereby increasing the maximum strain that the actuator can produce. In this work, a new technique developed for plating metal particulates on the surface of ionomeric materials is applied to the development of hybrid transducers that incorporate carbon nanotubes and conducting polymers as electrode materials. The new plating technique, named the direct assembly process, consists of mixing a conducting powder with an ionomer solution. This technique has demonstrated improved response time and strain output as compared to previous methods. Furthermore, the direct assembly process is less costly to implement than traditional impregnation-reduction methods due to less dependence on reducing agents, it requires less time, and is easier to implement than other processes. Electrodes applied using this new technique of mixing RuO2 (surface area 45~65m2/g) particles and Nafion dispersion provided 5x the displacement and 10x the force compared to a transducer made with conventional methods. Furthermore, the study illustrated that the response speed of the transducer is optimized by varying the vol% of metal in the electrode. For RuO2, the optimal loading was approximately 45%. This study shows that carbon nanotubes electrodes have an optimal performance at loadings around 30 vol%, while PANI electrodes are optimized at 95 vol%. Due to low percolation threshold, carbon nanotubes actuators perform better at lower loading than other conducting powders. The addition of nanotubes to the electrode tends to increase both the strain rate and the maximum strain of the hybrid actuator. SWNT/RuO2 hybrid transducer has a strain rate of 2.5%/sec, and a maximum attainable peak-to-peak strain of 9.38% (+/- 2V). SWNT/PANI hybrid also increased both strain and strain rate but not as significant as with RuO2. PANI/RuO2 actuator had an overwhelming back relaxation.